Tourism as Devotion: Understanding Religious and Spiritual Travel Experiences in Indonesia - Sumandi, Sumandi (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2024)
This study explores the ways in which religious and spiritual practices shape tourism experiences in Indonesia, focusing on how devotion, ritual, and meaning-making intersect with travel. Religious tourism, encompassing pilgrimages, visits to sacred sites, and ritual participation, has become a growing segment of Indonesia’s tourism landscape, reflecting the country’s diverse spiritual traditions. Using a qualitative design, fieldwork was conducted at Islamic pilgrimage destinations in Lombok and Hindu temple sites in Bali, combining semi-structured interviews with pilgrims, local guides, and community leaders, alongside participant observation of ritual practices. Thematic analysis revealed three major dimensions of religious and spiritual tourism. First, participants described motivations rooted not in leisure but in faith obligations, spiritual renewal, and the search for blessings. Second, the experience of ritual participation provided a sense of communal belonging and emotional uplift, demonstrating how tourism can reinforce religious identity. Third, tensions emerged between devotion and commercialization, as some visitors expressed discomfort with the commodification of sacred spaces through ticketing, souvenirs, or staged performances. The findings suggest that religious tourism in Indonesia is not only a cultural and economic practice but also a deeply embodied form of devotion, where faith and travel converge to produce transformative experiences.